Parasitic development in intestines and oocyst shedding patterns for infection by Eimeria uekii and Eimeria raichoi in Japanese rock ptarmigans, Lagopus muta japonica, protected by cages in the Southern Japanese Alps - Makoto Matsubayashi; Moemi Kinoshita; Atsushi Kobayashi; Sayaka Tsuchida; Tomoyuki Shibahara; Masami Hasegawa; Hiroshi Nakamura; Kazumi Sasai; Kazunari Ushida (International Journal for Parasitology: Parasites and Wildlife, 2020)
The population of Japanese rock ptarmigan (Lagopus muta japonica), an endangered species with a habitat above the timberline of the southern Japanese Alps, has declined. As one of the recent conservation strategies for this species, cage protection for broods (hens and chicks) has been introduced in their habitats. Two species of Eimeria have frequently been detected in these birds, but little is known about the parasitic circulation in the region, including among birds and in the environment. Here, we conducted histopathology examinations of dead chicks collected under cage protection in 2018, and examined the feces of the hens and chicks of three broods and environmental soils for parasites in 2019 in order to assess the potential sources of infection and pathogenicity. Developmental zoites were found in the epithelial mucosa and/or the submucosa from the duodenum to the colon of all dead chicks. Fecal examination revealed oocysts of E. uekii and/or E. raichoi in all hens and chicks. Oocysts of Eimeria spp. per gram of feces in chicks increased within 2 weeks after hatching and then gradually deceased. Following infection of the chicks, oocysts could accumulate within the cage areas, and oocyst density exceeded more than 1000 oocysts per gram of cage soils. Based on having sporulated morphologies, oocysts could be infective and therefore, be direct or indirect potential sources of infection. However, based on our findings that not all chicks were clinically affected by the infections, other factors such as microbial flora in the chicks established by coprophagy or from the habitat environment, including climate, might be associated with the pathogenicity of Eimeria spp., although further studies are needed to assess these correlations.